Preliminary analysis of benzene, toluene, ethylbenzene, O-Xylene (BTEX) and formaldehyde inside vehicle cabin / Noor Hafiz Noordin ... [et al.] - Noordin, Noor Hafiz; Abd Razak, Azli; Kushairi, Sahril; Mohamad, Mohd Faizal (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Vehicle indoor air quality (VIAQ) has become a high important field of research since people spend much of their time inside vehicle cabin. Volatile organic compounds (VOCs) are one of the main pollutants inside vehicle cabin. There are various types of VOCs can be found inside vehicle cabin and high exposure to these organic compounds may affect the human health. This study was conducted to analyse the effect of indoor temperature to the concentration of formaldehyde, benzene, toluene, ethylbenzene and o-xylene inside vehicle cabin when a vehicle was parked under direct sunlight and driven under different ventilation modes. Among the sampling methods used in indoor air quality research, direct-reading instrument and active air sampling are the methods usually applied to measure the air quality level inside vehicle cabin. This study used direct-reading instrument to measure the concentration of formaldehyde and active air sampling to identify the concentration of benzene, toluene, ethylbenzene and o-xylene (BTEX). It was found that high indoor temperature with heat accumulation accelerated the melting process of interior material; thus, causing a high emission of formaldehyde concentration inside vehicle cabin. The role of ventilation modes was more dominant compared to indoor temperature. Meanwhile, the concentrations for BTEX were not detected possibly due to age of studied vehicle.